Convenient Clothing Pattern and Colour Recognition for People with Vision Impairment - kumar.R, Vijay; V, Vishwas.; M, Bharath.; kumar.R, Yathish; S, Veena. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The objective of this paper is to design andimplement a prototype which is capable of recognizingclothing patterns in four categories(plaid,plain,irregular,striped) and identifies 12 colors.Choosing clothes with complex patterns and colors is achallenging task for visually impaired people. We havedeveloped a camera-based prototype system that hasan integrated camera, a microphone, a computer, and aBluetooth earpiece for audio description of clothing patternsand colors. The clothing patterns and colors are described toblind users orally. This system can be controlled by speechinput through microphone. To recognize clothing patterns, wepropose a novel Radon Signature descriptor and a schema toextract statistical properties from wavelet sub-bands tocapture global features of clothing patterns. To evaluate theeffectiveness of the proposed approach, we used the CCNYClothing Pattern dataset. Our approach achieves 90%recognition accuracy which significantly outperforms thestate-of-the-art texture analysis methods on clothing patternrecognition.